Marketing today's academic library a bold new approach to communicating with students - Mathews, Brian (Brian Scott) (IG library, 2009)
In this study, Brian Mathews uses his vast experience to speak directly to the academic library practitioner about matching services with user needs. This book proposes new visions and ideas, challenging the traditional way of thinking and providing a framework to target users more precisely.